PdFeCo Supported on N-rGO as a Bifunctional Catalyst for Methanol Oxidation and High Stability Oxygen Reduction Reaction - Frizka Vietanti; Chen-Hao Wang (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2020)
In this study, we have synthesized nitrogen doped reduced graphene oxide (N-rGO) supported ternary PdFeCo nanoparticle by three methods. A hydrothermal method to synthesize N-rGO, an emulsion method to synthesize PdFeCo nanoparticle, and a rota-evaporation to synthesize PdFeCo/N-rGO composite. A bifunctional PdFeCo/N-rGO exhibited excellent electrocatalytic activity towards both methanol oxidation and stability in oxygen reduction reaction (ORR). During methanol oxidation reaction, PdFeCo/N-rGO exhibited stronger methanol tolerance than Pt/C. In stability ORR, PdFeCo/N-rGO exhibited 2.85 times greater than Pt/C  in ORR stability. The high performance of PdFeCo/N-rGO was attributed by strong bonding of structure. A strong bonding of transition metals in Pd based catalyst can servemethanol tolerance and stability during ORR activity.